2016
DOI: 10.1002/sys.21336
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Systems Engineering in Civil Engineering Consulting Firm: An Evaluation

Abstract: This study explores the challenges that civil engineering consulting firms face in their projects when they apply Systems Engineering (SE). It is also explained were these firms should focus when improving the use of SE. To conduct this study, the methodology of Eisenhardt (Building theories from case study research, Acad Manage Rev 14 [1989], 532-550) for building theory from case study research is used. The extent, to which SE is applied, is assessed in six civil engineering projects, using a newly developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The importance of knowledge and skills to improve SE practices is mentioned in SE literature as well (Sheard et al ., ; Bonnema et al ., ; Van Nederveen et al ., 2008; Bhasin et al ., ; Godfrey et al ., ; De Graaf et al ., ; De Graaf et al ., ). For example, in their article on SE process improvement, Sheard et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The importance of knowledge and skills to improve SE practices is mentioned in SE literature as well (Sheard et al ., ; Bonnema et al ., ; Van Nederveen et al ., 2008; Bhasin et al ., ; Godfrey et al ., ; De Graaf et al ., ; De Graaf et al ., ). For example, in their article on SE process improvement, Sheard et al .…”
Section: Discussionmentioning
confidence: 97%
“…De Graaf et al . () also found that in projects carried out by an engineering consulting firm, SE tasks were carried out inadequately because team members had not been given enough training. This, in turn, was due to the time pressure of the project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the five risk management objectives of "safety, quality, construction period, cost, and environment" are used as the evaluation criterion layer, and then the risk factors are identified to establish the evaluation index layer. The specific methods are as follows: (1) Systematically sort out the whole process engineering consulting cases and related research documents [6][7][8], and analyze the construction accidents that have occurred in recent years; (2) Combining the analysis results, according to the "Technical Standards for Engineering Consulting Services for the Whole Process of Housing Construction and Municipal Infrastructure Construction Projects" (draft for comments), from the survey, Design, bidding, procurement, and supervision to extract the main risk factors that affect the life cycle consulting of engineering construction. (3) Through questionnaire surveys, collect opinions on risk factors from experts in the construction, design, and consulting fields of the construction industry.…”
Section: Setting Of Evaluation Criteria and Rating Indicatorsmentioning
confidence: 99%
“…For example, the magazine “INSIGHT” has published a special issue on infrastructure SE, including articles on the civil engineering industry . Handbooks and guidelines have also appeared in the past 15 years, such as the “Guide for the Application of SE in Large Infrastructure Projects,” the guidebook on SE in the civil engineering industry in The Netherlands, and the “Systems Engineering Guidebook for Intelligent Transportation Systems.” Moreover, articles have been published in which the use of SE in specific civil engineering projects is discussed . Finally, SE in the civil engineering industry is considered in relation to education and training and procurement .…”
Section: Introductionmentioning
confidence: 99%